PENERAPAN MODEL PEMBELAJARAN THINK PAIR SHARE (TPS) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS VI - Mikail Mikail (PENBIOS: JURNAL PENDIDIKAN BIOLOGI DAN SAINS, 2019)
This study aims to improve the learning outcomes of Grade VI students in science subjects with the subject matter of the breeding of living things using Think Pair Share Learning Model (TPS). This research is a class action research. The subject of this study was class VI SDN 3 Jereweh with 25 students taking place in three cycles and each consisting of 3 meetings. Data collection techniques in this study were observation and tests. The results of classroom action research by applying a think pair share learning model indicate that student science learning outcomes have increased. This is indicated by an increase in the average value of the class at the time of cycle 1 the average value of 74.28; 76.74 in cycle 2, and 87 in cycle 3, while classical completeness increases 24% from cycle 1 to cycle 2, and from cycle 2 to cycle 3 32%. The conclusion from the results of this study is that the Think Pair Share (TPS) Learning Model has been proven to have improved the learning outcomes of Grade VI students in science subjects.